2023
DOI: 10.3389/fpubh.2023.1297770
|View full text |Cite
|
Sign up to set email alerts
|

Primary healthcare workers’ COVID-19 infection status following implementation of adjusted epidemic prevention and control strategies: a cross-sectional study in Jiangsu, China

Beier Lu,
Rongji Ma,
Jinshui Xu
et al.

Abstract: IntroductionIn times of epidemic outbreaks, healthcare workers (HCWs) emerge as a particularly vulnerable group. This cross-sectional study endeavors to assess the COVID-19 infection rate among the primary HCWs in Jiangsu Province subsequent to the implementation of adjusted epidemic prevention and control strategies.MethodsFrom January 17 to February 2, 2023, an extensive survey was conducted among primary HCWs in Jiangsu Province, employing a self-designed questionnaire. Logistic regression analysis was util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Throughout the pandemic, primary healthcare facilities faced numerous challenges, including a surge in patient numbers, resource limitations, and service disparities. Research has demonstrated that optimizing resource allocation, strengthening human resource management, implementing digital healthcare solutions (9)(10)(11), and boosting community engagement can substantially improve service efficiency and alleviate epidemicrelated pressures. Nonetheless, technical, policy, and sociocultural hurdles continue to impede efficiency enhancements.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the pandemic, primary healthcare facilities faced numerous challenges, including a surge in patient numbers, resource limitations, and service disparities. Research has demonstrated that optimizing resource allocation, strengthening human resource management, implementing digital healthcare solutions (9)(10)(11), and boosting community engagement can substantially improve service efficiency and alleviate epidemicrelated pressures. Nonetheless, technical, policy, and sociocultural hurdles continue to impede efficiency enhancements.…”
Section: Introductionmentioning
confidence: 99%